CT-based total vessel plaque analyses improves prediction of hemodynamic significance lesions as assessed by fractional flow reserve in patients with stable angina pectoris - Ovrehus, Kristian A.; Gaur, Sara; Leipsic, Jonathon; Jensen, Jesper M.; Dey, Damini; Botker, Hans E.; Ahmadi, Amir; Achenbach, Stephan; Ko, Brian; Norgaard, Bjarne L. (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: Coronary stenosis and plaque evaluation by coronary computed tomography angiography (CTA) may contribute to identify hemodynamically relevant lesions. We evaluated the most stenotic lesion including plaques proximal to it versus a total vessel analyses combined with stenosis for ischemia. METHODS: Patients scheduled for clinically indicated invasive coronary angiography (ICA) for suspected coronary artery disease underwent coronary CTA and ICA including fractional flow reserve (FFR) as part of the NXT trial (clinicaltrials.govNCT01757678). Stenoses were visually graded ≤50%, 51-70%, and >70% on coronary CTA. Semi-automated plaque analyses were performed using a proximal to the FFR pressure sensor location (including the most severe lesion to the coronary ostium) versus a total vessel (vessel diameter ≥2 mm) approach. Coronary stenosis and plaque parameters were evaluated for discrimination of ischemia by logistic regressions and combined models analyzed using receiver operating characteristics (ROC) with invasive FFR≤ 0.80 as reference standard. RESULTS: In 254 patients, mean (±SD) age 64 (±10) years, 64% male, a coronary CTA stenosis >50% was present in 239 (49%) vessels. Invasive FFR was ≤0.80 in 100 (21%) vessels. Coronary stenosis severity and low-density non-calcified plaque (LD-NCP) volume were independent predictors of ischemia in the "proximal" and "total-vessel" analyses. Stenosis severity + total vessel LD-NCP assessment performed better than stenosis severity + proximal LD-NCP evaluation (Area under curve [AUC] (95%CI): 0.83 (0.78-0.87) vs 0.81 (0.76-0.86), p-value = 0.009), whereas stenosis severity + proximal LD-NCP performed better than stenosis alone (AUC (95%CI): 0.81 (0.76-0.86) vs 0.78 (0.73-0.83), p-value = 0.019). CONCLUSION: Adding total vessel high-risk plaque volume to stenosis severity improves discrimination of ischemia in coronary CTA performed in patients with stable angina pectoris.
EVALuna2:35980